PERBEDAAN ASUPAN ZAT GIZI MAKRO, POLA MAKAN DAN IMT/U PADA SANTRIWATI BOARDING SCHOOL YANG MEMILIKI AHLI GIZI DAN TANPA AHLI GIZI - Idiara Setya Yusdika (2023)
The existence of nutritionist is still uncommon to be applied in Boarding Schools for the purpose of maintaining and enhancing students' nutritional intakes. The goal is to analyzed the differences of macronutrients intake (energy, carbohydrates, proteins, and fats), eating habit, and IMT of the students in Boarding Schools with and without nutritionists. The research was analyzed by using quantitative and cross sectional design with the amount of samples are 79 respondents from each Boarding Schools, resulting the total of the respondents are 158 students. Stratisfied random sampling technique was applied to choose the respondents. The data were analyzed with Mann Whitney for numerical data and chi square for category data. The results are there are the differences between energy intake (p-value = 0,0,010), fat intake (p-value=0,008), cabohydrate intake (p-value = 0,000) and there are no differences between protein intake (p-value=0,760), Eating pattern (p-value=1,000), BMI (p-value=0,316) of Al Hamidiyah students and Dwiwarna Boarding School students. The role of nutritionists needs to be improved, specifically in counseling and monitoring the management of meal service and intake for boarding school students.